Perubahan Tradisi Upacara Adat Pernikahan Etnis Melayu Deli di Desa Paluh Sibaji Kecamatan Pantai Labu Kabupaten Deli Serdang - Sylvia, Cici; Nursetiawati, Sitti; Dudung, Agus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to determine the changes in the tradition of the Deli Malay ethnic wedding ceremony in Paluh Sibaji Village. Changes that occur in the tradition of traditional wedding ceremonies are not only influenced by the times, but are also caused by the tradition of recording or recording knowledge about traditional marriage ceremonies which are rarely encountered. The traditional Deli Malay wedding ceremony at the present time in Paluh Sibaji Village has undergone many changes and is very different from the previous Deli Malay wedding ceremony. This research is a qualitative research with ethnographic method. Qualitative research design consists of three stages of data collection, analysis and interpretation, manufacture. The research data are in the form of library research, interviews, results of field observations and documentation. Based on the results of observations, interviews, and documentation by researchers, the traditional Malay deli wedding ceremony tradition in Paluh Sibaji village has undergone changes. The researcher also found the complete implementation of the Malay Deli traditional wedding ceremony at the Maimun Palace. Some of the changes that occurred in the tradition of the Malay Deli wedding ceremony because it was adjusted to the teachings of the Islamic religion. There are slight differences in each series of traditional Malay deli wedding ceremonies in each region, although there are differences, the red line remains the same.